An Overview of Development in Translation Theory (Texas Journal of Philology, Culture and History, 2024)
One invaluable activity that unites communities and individuals and facilitates communication and conversation is the process of translation. It goes all the way back to the dawn of human history. Since translation science is founded on a wide range of historical processes, there are many variables to consider when defining the word "translation process." By the second half of the 20th century, it was widely accepted that morphological aspects of texts needed special attention and that artistic influences in written texts might not be fully understood by the intended audience. As a result, linguistic approaches that were oriented toward the source text were used. The source text serves as the criterion in this method. Translators that have this knowledge base their translations solely on the words they are translating, without considering the overall context of the text. The target culture reader is not expected to be as impacted by source text-oriented translation as the source culture reader is.